Essential training for a better fisheries integrated management - Izadian B. (Food security under water scarcity in the Middle East: Problems and solutions, 2005)
Operational planning and management system in a fishing harbour describes how different components of facilities, people, and administrative structure work together to meet customer expectations. However, it is essential to invest on human capital for implementation of this practical system as many regional nations are experiencing problems with recruitment and retention of managers not received appropriate training in fisheries harbour management. Redesigning curricula and training programs may only be part of the solution to build human capital. Attracting people with intellect and abilities requires a work environment that provides appropriate freedoms, responsibilities, and rewards. This paper tries to identify essential training and the gaps between those supplying them and regions in demand.
LNCV [Landau Network-Centro Volta] International Forum: Food Security under Water Scarcity in the Middle East: Problems and Solutions, 24-27 Nov 2004, Como (Italy)